2022
DOI: 10.1007/s10900-022-01111-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Viral Hepatitis in Unselected, Consecutively Enrolled Patients Hospitalised for SARS-CoV-2

Abstract: Diagnosing people living with chronic viral hepatitis is challenging due to the absence of symptoms as long as liver decompensated cirrhosis come out. The aim of this retrospective study was to evaluate the prevalence of HBV and/or HCV infections in a non-selected population, hospitalised for SARS-CoV-2 infection in a tertiary care hospital in Northern Italy. During the study period 1,429 patients were admitted to hospital for SARS-CoV-2 infection, serologic tests for HBV and/or HCV were available for 382 (27%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Another point raised by our study is the high percentage of subjects with positive anti‐HCV but negative HCV–RNA values (71.7%). This data is in line with other reports, as rates of undetectable HCV–RNA in anti‐HCV positive subjects identified by opportunistic screening programs in recent studies vary between 64% and 82%, 11–14 to be lower in individuals unaware of their status (0%–33%) 8,17,12–14 . Although patients with a sustained virological response (SVR) should not have been included in our study, we cannot exclude that some of them did still participate to this screening program.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another point raised by our study is the high percentage of subjects with positive anti‐HCV but negative HCV–RNA values (71.7%). This data is in line with other reports, as rates of undetectable HCV–RNA in anti‐HCV positive subjects identified by opportunistic screening programs in recent studies vary between 64% and 82%, 11–14 to be lower in individuals unaware of their status (0%–33%) 8,17,12–14 . Although patients with a sustained virological response (SVR) should not have been included in our study, we cannot exclude that some of them did still participate to this screening program.…”
Section: Discussionsupporting
confidence: 91%
“…Another point raised by our study is the high percentage of subjects with positive anti-HCV but negative HCV-RNA values (71.7%). This data is in line with other reports, as rates of undetectable HCV-RNA in anti-HCV positive subjects identified by opportunistic screening programs in recent studies vary between 64% and 82%, [11][12][13][14] to be lower in individuals unaware of their status (0%-33%). in Milan, 4 out of 5 (80%) positive subjects initially affirming to be unaware of their HCV status declared to have already been treated…”
Section: Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of 3.1% HBsAg that we found in our study of outpatients presenting with COVID-19 at a tertiary care hospital in Romania is in line with the data previously reported for Romania, which placed the country at intermediate prevalence, with 4.4% of the general population testing positive for HBsAg, [ 11 ] and higher than that reported from a comparable study performed in Italy in a slightly smaller patient group, where 0.5% of 372 patients tested positive for HBsAg. [ 12 ] In our study, only six of our 16 HBsAg-positive patients were aware of their HBV status, and the overall rate of new HBV diagnoses was 1.9% in the entire patient cohort, suggesting that there might be quite a large proportion of undiagnosed patients that we still need to actively identify and link to care. Importantly, one third of these newly diagnosed cases of HBV infection also met the criteria for starting antiviral treatment, highlighting the need for earlier access to screening, to allow timely therapeutic intervention.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, we found a high prevalence (23%) of anti-HBc, indicative of past HBV infection, higher than the prevalence of 17% reported among 320 subjects from a similar patient population tested in Italy. [ 12 ] The following patient characteristics were considered to be highly suggestive for history of prior HBV infection and should trigger an in-depth liver and viral hepatitis workup: older age, hypoalbuminemia, decreased platelet counts either alone or followed by increased platelet counts at day 14, and increased lactate dehydrogenase. We further found that patients with evidence of prior HBV infection displayed particular dynamics of liver-related laboratory parameters over the course of COVID-19, specifically: higher liver cytolysis (increased transaminases) and cholestasis (increased bilirubin), lower ALB levels, and lower platelet counts, compared to patients without evidence of prior HBV infection; they also displayed higher BUN levels, indicating the need to closely follow the kidney function in this subset of patients.…”
Section: Discussionmentioning
confidence: 99%